3x + 3y + 6z = 9
2x + 1y + 3z = 7 ⇒ 6x + 6y + 8z = 6
1x + 2y - 1z = -10 6x + 6y + 8z = 6
4z = 12
3x + 3y + 6z = 9 4 4
2x + 1y + 3z = 7 ⇒ 0x + 0y + 4z = 12 z = 3
1x + 2y - 1z = -10 2x + y = -2
2x + (-4) = -2
2x - 4 = -2
+ 4 + 4
2x = 2
2 2
x = 1
(x, y, z) = (1, -4, 3)
I don’t even know 5x 15 equals 7 because 12inches is a feet
Answer:
x=9
Step-by-step explanation:
x+18=2x+9
-x -x
18=x+9
-9 -9
9=x
x=9
Step-by-step explanation:
2a - 7 - 6a = 9
- 4a - 7 = 9
- 4a = 16
a = -4
Answer:
yes, ±2
Step-by-step explanation:
The x-intercepts are found by setting y=0 and solving for x:
x^2/4 = 1
x^2 = 4
x = ±√4
x = ±2
The x-values of interest are -2 and +2.